Impact of thrombocytopenia on failure of endoscopic variceal treatment in cirrhotic patients with acute variceal bleeding - Yan He; Fernando Gomes Romeiro; Mingyu Sun; Fanpu Ji; Qiang Zhu; Yingli He; Dapeng Ma; Shanshan Yuan; Xiaofeng Liu; Cyriac Abby Philips; Metin Basaranoglu; Nahum Méndez-Sánchez; et al. (Therapeutic Advances in Gastroenterology)
Background: Acute variceal bleeding (AVB), a life-threatening complication of liver cirrhosis, can be effectively treated by endoscopy, but there is a risk of early rebleeding after endoscopic variceal treatment (EVT). Thrombocytopenia is the most common hemostatic abnormality in liver cirrhosis. However, it is still unclear about whether thrombocytopenia increases the failure of EVT in cirrhotic patients with AVB. Objectives: We investigated the association between thrombocytopenia and the failure of EVT in cirrhotic patients with AVB. Design: International multicenter, retrospective study. Methods: Overall, 2467 cirrhotic patients with acute gastrointestinal bleeding who were enrolled into an international multicenter study between September 30, 2020 and June 30, 2023 were retrospectively screened. Thrombocytopenia was defined as platelet count below 150 × 10 9 /L and further classified as mild (100 × 10 9 /L–150 × 10 9 /L), moderate (50 × 10 9 /L–100 × 10 9 /L), and severe (<50 × 10 9 /L). A 1:1 propensity score matching (PSM) analysis was performed. Five-day failure to control bleeding was evaluated. Results: Overall, 1079 patients were included, of whom 923 (85.5%) had thrombocytopenia, including mild ( n  = 241), moderate ( n  = 445), and severe ( n  = 237) thrombocytopenia. PSM analysis demonstrated that the rate of 5-day failure to control bleeding was not significantly different between patients with and without thrombocytopenia (mild: (12/153) 7.8% vs (7/153) 4.6%, p  = 0.236; moderate: (9/155) 5.8% vs (7/155) 4.5%, p  = 0.608; or severe: (5/132) 3.8% vs (7/132) 5.3%, p  = 0.555). Conclusion: Thrombocytopenia may not influence the efficacy of EVT in cirrhotic patients with AVB.